(untitled) (Global Journal of Medical Research, 2020)
Tuberculosis is an infectious disease with high incidence and mortality rates in the world. TB not only attacks lung, but other organs called Extrapulmonary Tuberculosis (EPTB) as well. At present, the diagnostic for EPTB is challenging since there are many examinations needed. This study developed a scoring system for EPTB diagnosis based on some parameters. The parameters derived from our studies evaluating AFB stain examination of biopsy tissue associated with the clinical feature of EPTB patients. Parameter included a detailed medical history and clinical examination, radiological, microbiological, molecular, and histopathological investigations. The proposed scoring system used a minimum android version of jellybean 4.1. The application is simple to accommodate users’ low ability to operate. The scoring system is proposed for accommodating many parameters important for diagnostic. It differentiates which conditions are highly suspicious and should be included in the differential diagnosis. EPTB Scoring system can be an alternative for EPTB diagnostic tools.